A novel flexible micro-ratchet/ZnO nano-rods surface with rapid recovery icephobic performance - Wang, Manxiang; Yu, Wenbo; Zhang, Yupei; Woo, Jae-Young; Chen, Yu; Wang, Bo; Yun, Yanbin; Liu, Guicheng; Lee, Joong Kee; Wang, Lei (한국공업화학회, 2018)
In this communication, we present a significant method to fabricate a robust icephobic surface on a flexible polymer substrate. The flexible functional surface is obtained by integrating both soft lithography and crystal growth methods. Modified by the materials with low surface free energy, the composite surface exhibits a robust superhydrophobicity at not only room temperature but also low temperature. After freezing test, the surface can recover to its original function quickly, which has achieved the level for industrial application, and also performed significant role for enhancing the icephobic theories. (C) 2018 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.